Long-term outcomes after hypothermic oxygenated machine perfusion and transplantation of 1,202 donor livers in a real-world setting (HOPE-REAL study) - Eden, Janina; Brüggenwirth, Isabel M A; Berlakovich, Gabriela; Buchholz, Bettina M; Botea, Florin; Camagni, Stefania; Cescon, Matteo; Cillo, Umberto; Colli, Fabio; Compagnon, Philippe; De Carlis, Luciano G; De Carlis, Riccardo; et al. (Journal of hepatology, 2025)
BACKGROUND & AIMS: Despite strong evidence for improved preservation of donor livers by machine perfusion, longer post-transplant follow-up data are urgently needed in an unselected patient population. We aimed to assess long-term outcomes after transplantation of hypothermic oxygenated machine perfusion (HOPE)-treated donor livers based on real-world data (i.e., IDEAL-D stage 4). METHODS: In this international, multicentre, observational cohort study, we collected data from adult recipients of HOPE-treated livers transplanted between January 2012 and December 2021. Analyses were stratified by donation after brain death (DBD) and donation after circulatory death (DCD), sub-divided by their respective risk categories. The primary outcome was death-censored graft survival. Secondary outcomes included the incidence of primary non-function (PNF) and ischaemic cholangiopathy (IC). RESULTS: We report on 1,202 liver transplantations (64% DBD) performed at 22 European centres. For DBD, a total number of 99 benchmark (8%), 176 standard (15%), and 493 extended-criteria (41%) cases were included. For DCD, 117 transplants were classified as low risk (10%), 186 as high risk (16%), and 131 as futile (11%), with significant risk profile variations among centres. Actuarial 1-, 3-, and 5-year death-censored graft survival rates for DBD and DCD livers were 95%, 92%, and 91%, vs. 92%, 87%, and 81%, respectively (log-rank p = 0.003). Within DBD and DCD strata, death-censored graft survival was similar among risk groups (log-rank p = 0.26, p = 0.99). Graft loss due to PNF or IC was 2.3% and 0.4% (DBD), and 5% and 4.1% (DCD). CONCLUSIONS: This study shows excellent 5-year survival after transplantation of HOPE-treated DBD and DCD livers with low rates of graft loss due to PNF or IC, irrespective of their individual risk profile. HOPE treatment has now reached IDEAL-D stage 4, which further supports its implementation in routine clinical practice. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT05520320. IMPACT AND IMPLICATIONS: This study demonstrates the excellent long-term performance of hypothermic oxygenated machine perfusion (HOPE) treatment of donation after circulatory and donation after brain death liver grafts irrespective of their individual risk profile in a real-world setting, outside the evaluation of randomised-controlled trials. While previous studies have established safety, feasibility, and efficacy against the current standard, according to the IDEAL-D evaluation framework, HOPE treatment has now reached the final IDEAL-D stage 4, which further supports its implementation in routine clinical practice.
Keywords: DHOPE; Humans; lidé středního věku; Hypothermia, Induced; machine preservation; kohortové studie; machine perfusion; uchovávání orgánů; Female; Aged; hypothermic oxygenated machine perfusion; dospělí; přežívání štěpu; výsledek terapie; Tissue Donors; senioři; lidé; IDEAL stage 4; Perfusion; Cohort Studies; Liver Transplantation; Organ Preservation; transplantace jater; Adult; dárci tkání; ženské pohlaví; Male; Middle Aged; perfuze; Treatment Outcome; long-term outcome; HOPE; liver transplantation; mužské pohlaví; Graft Survival; terapeutická hypotermie